Factors Associated with the Level of Knowledge about Dental and Oral Health of Students of SD 27 Kedai Durian Village Medan - Novzi, Nanda; Mayasari Ramadhani; Tezar Samekto Darungan; Mayangsari Ayu; Farah Diba (Institut Kesehatan Medistra Lubuk Pakam, 2025)
The state of the mouth cavity is one sign of a person's general health. Finding the elements that affect SD 27 kids' development and maintenance of excellent oral health is the aim of this study. With a cross-sectional methodology and an analytical research strategy, the study included 67 participants who were chosen by primary data sampling. The findings showed that most of the respondents (n = 44, 65.7%) were between the ages of 5 and 11. Furthermore, the vast majority of participants (n = 41, 61.2%) reported that they had obtained information via electronic media. Moreover, a high degree of expertise was demonstrated by the majority of responders (n = 52, 77.6%). Most respondents (n = 38, 56.7%) who showed a high degree of understanding were between the ages of 5 and 12. Age and children's degree of oral health knowledge were shown to be significantly correlated (p = 0.017). Similarly, a significant correlation (p = 0.012) was found between the amount of oral health knowledge and the information source.